Peraturan Hukum Pidana Anak Akibat Kecelakaan Lalu Lintas - Mutriady, Anto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this study was to analyze the strategies for resolving traffic accidents of child offenders with distraction in Medan. The research method used was a qualitative method approach. The results of this study indicate that traffic accident descriptions are the most dominant ones caused by children and adolescents, who then propose diversion methods or approaches. The constraints in implementing child offender trafficking settlement are public understanding of diversion, thinking between victims and parties in conflict with the law to reach an agreement and different understandings in handling children in conflict with the law among law enforcement officers. Strategies for addressing child traffic accidents with diversion approaches in Medan are holding socialization on diversion among the community, efforts to unite thinking between victims and children in conflict with the law to reach agreement and build intensive communication with other law enforcement officers.